1 1/6
Пошаговое объяснение:
- 0.5(x - 4 1/5) - 7/15 * (2 - 1 1/14 x) = 1 1/6
По действиям:
1. -0.5(x - 4 1/5) = -1/2(x - 21/10) = -1/2*х - (-1/2)*21/10 = -1/2х + 2 1/10
2. 7/15 * (2 - 1 1/14 x) = 7/15*(2 - 15/14x) = 7/15*2 - 7/15*15/14х =
14/15 - 7/14х = 14/15 - 1/2х
3. -1/2х + 2 1/10 - (14/15 - 1/2х) = -1/2х + 2 1/10 - 14/15 + 1/2х =
2 1/10 - 14/15 = 2 3/30 - 28/30 = 1 33/30 - 28/30 = 1 5/30 = 1 1/6
1 1/6
Пошаговое объяснение:
- 0.5(x - 4 1/5) - 7/15 * (2 - 1 1/14 x) = 1 1/6
По действиям:
1. -0.5(x - 4 1/5) = -1/2(x - 21/10) = -1/2*х - (-1/2)*21/10 = -1/2х + 2 1/10
2. 7/15 * (2 - 1 1/14 x) = 7/15*(2 - 15/14x) = 7/15*2 - 7/15*15/14х =
14/15 - 7/14х = 14/15 - 1/2х
3. -1/2х + 2 1/10 - (14/15 - 1/2х) = -1/2х + 2 1/10 - 14/15 + 1/2х =
2 1/10 - 14/15 = 2 3/30 - 28/30 = 1 33/30 - 28/30 = 1 5/30 = 1 1/6